Antiviral Activities of Mulberry (Morus alba) Juice and Seed against Influenza Viruses. (1st November 2018) - Kim, Hyojin; Chung, Mi Sook
Abstract : Antiviral activities of Morus alba (MA) juice and seed were examined using time-of-addition plaque assays against influenza viruses, A/Brisbane/59/2007 (H1N1) (BR59), pandemic A/Korea/01/2009(H1N1) (KR01), A/Brisbane/10/2007(H3N2) (BR10), and B/Florida/4/2006 (FL04). MA juice (MAJ) showed much higher antiviral activity than MA seed (MAS). In the pre- and cotreatment of virus, MAJ showed antiviral effects against BR59, KR01, and FL04 in a dose-dependent manner. In particular, MAJ at 4% concentration exhibited 1.3 log inhibition in the pre- and cotreatment of the virus against FL04, a type B virus. However, little or weak inhibition was observed in the posttreatment of MAJ. GSH levels in the virus-infected cells were also examined. The decreased levels by the viral infection were restored significantly by the addition of MAJ. MAJ also exhibited significant DPPH radical scavenging and ferric ion-reducing activities in a dose-dependent manner. Cyanidin-3-rutinoside, the most abundant polyphenol compound of MAJ identified by LC-MS in this study, showed weak inhibitory effects against FL04 in the pretreatment, whereas gallic acid, a minor compound of MAJ, revealed significant antiviral effect. These results suggest that MAJ can be developed as a novel plant-derived antiviral against influenza viruses.